Upaya Peningkatan Kompetensi Perempuan di Desa Karangkepoh melalui Pemanfaatan Pangan Lokal untuk Pemenuhan Gizi Seimbang - Achmad Januar Arifin; Sadna Izzatul Azka; Niken Diah Haryanti; Isnaindita, Oktadella Maulida Nur; Arief Setiadi; Safitri, Sylviana Ika; Rabbani, Khafidh Fardhan; Fitri Yana Nia Ramadhani; Naila Ayu Kharisma; Nila Dwi Yanti; Prakas Bima Saputra; Fadhil Huzaifi Nawal; Calista Amalia Setiaji; Siti Maisarah; Muhammad Qodar Ansori; Ika Candra Sayekti (Warta LPM, 2025)
A low level of nutritional knowledge in a mother can be a determining factor in the nutritional status of the family because it will affect how she chooses the type of food, the amount, and how often the food is consumed by her family. The objectives of this community service program in Karangkepoh Village, Boyolali Regency are 1) to increase the competence of women in Karangkepoh Village about balanced nutrition materials, 2) to increase the knowledge of women in Karangkepoh Village about balanced nutrition materials. and 3) shaping balanced nutrition behavior in Karangkepoh Village. The implementation methods used were 1) observation and interview methods, 2) socialization methods, 3) practical methods and 4) monitoring and evaluation methods. Data analysis techniques were carried out through observation sheets, interview sheets, and questionnaires. The results of this socialization activity consisted of 1) an increase in competence and activeness of mothers and adolescents in Karangkepoh Village. This is known by an increase in the percentage of data by 25% based on indicators of good food processing, 2) increased knowledge about balanced nutrition obtained a significant total percentage increase of 147.89%. The results of this data increase occurred because the mothers of Karangkepoh Village were very enthusiastic in listening to the material and asking questions during the socialization activities. 3) In the behavior of balanced nutrition or the application of balanced nutrition, it is known that there is an increase of 64.28% which is the highest increase compared to other indicators, the application of balanced nutrition has a high significance because in the statements in the pretest and posttest the mothers of Karangkepoh Village have applied the concept of balanced nutrition in their daily lives. Based on the average results of the Pre-test Post-test, it is known that there was an increase from the initial percentage of 260 to 345.